PROSPECTS FOR USING INTERNATIONAL EXPERIENCE FOR REFORMING THE PENSION SYSTEM OF UKRAINE - Martynenko , N. (Theory and Practice of Public Administration, 2020)
The article focuses on activities undertaken by developed countries - members of the European Union to determine ways of long-term development of pension systems. The analysis of pension reforms of the countries - members of the European Union (Sweden, Germany, Norway) showed that the key direction was to increase the financial stability of pension systems. Moreover, in the framework of the distribution level, the main emphasis was placed on reducing pension obligations by: increasing the retirement age, stimulating late retirement, tightening the conditions for early retirement, introducing stabilization mechanisms in the form of automatically increasing the retirement age in accordance with the increase in life expectancy after leaving retirement, raising the rate of contributions for retirement benefits.Carrying out institutional changes in the pension system of Ukraine, one should take into account the experience of the countries selected for the study in creating effective pension systems: the introduction of funded models with defined contributions (DC, or defined contribution) and conditional funded models (NDC, Notional Defined Contribution), the introduction of voluntary funded systems; development of additional individual retirement savings.The state of fulfillment of the most important tasks for the development of the pension system of Ukraine is analyzed, which were outlined in the Concept for the further implementation of the pension reform.The legislative and regulatory framework of Ukraine on the issues of pension provision requires improvement of the content, coherence among themselves and codification in order to maximize the settlement of pension relations and relations regarding the organization of their financing, overcoming contradictions and inconsistencies in existing norms, eliminating repetitions, gaps, duplication of norms. The development of the pension system of Ukraine requires further legislative activity and it should be based on a scientific basis.It was proposed to create an Interdepartmental Commission to conduct a comprehensive assessment of the pension system, develop the Concept of reforming the pension system and the Development Strategy of the pension system of Ukraine.